Review of the genus Ypsolopha Latreille, 1796 from China (Lepidoptera: Ypsolophidae) - Jin, Qing; Li, Houhun (Zootaxa, 2013)
We present a review of the Chinese species of the genus Ypsolopha Latreille. Of the 60 species treated herein, 21 species are described as new: Y. flaviterminata sp. nov., Y. flavida sp. nov., Y. albula sp. nov., Y. longisaccata sp. nov., Y. fascimaculata sp. nov., Y. mucronulata sp. nov., Y. bicostata sp. nov., Y. latiuscula sp. nov., Y. purpurata sp. nov., Y. minuta sp. nov., Y. allochroa sp. nov., Y. brevivalva sp. nov., Y. longifloccosa sp. nov., Y. paristrigosa sp. nov., Y. umbrina sp. nov., Y. varidentella sp. nov., Y. capitalba sp. nov., Y. triangula sp. nov., Y. aurea sp. nov., Y. chlorina sp. nov., and Y. bisticta sp. nov.; eight species are newly recorded for the Chinese fauna: Ypsolopha acerella Ponomarenko, Sohn et Zinchenko, Y. sarmaticella (Rebel), Y. albiramella (Mann), Y. altissimella (Chrétien), Y. albistriata (Issiki), Y. longa Moriuti, Y. saitoi Moriuti and Y. falcella (Denis & Schiffermüller). A new species-group, the albiramella-group, is defined. Ypsolopha hebeiensis Yang, Y. nigrofasciata Yang, Y. ulingensis Yang and Y. diana (Caradja) are redescribed. One synonym is established: Y. sordidella Sohn et Wu, 2010 syn. n. (= Y. sordida Sohn et Wu, 2010). The male genitalia of Y. japonica Moriuti, Y. altissimella (Chrétien), Y. diana (Caradja), and the female genitalia of Y. hebeiensis Yang, Y. sarmaticella (Rebel), Y. altissimella (Chrétien), Y. ulingensis Yang, Y. helva Sohn et Wu and Y. diana (Caradja) are described for the first time. Photographs of the adults, wing venations and genitalia are provided. Keys for the identification of species-groups as well as the species of each species-group are included, along with a distribution map of all the known Chinese species.